"Going beyond the recommended primary school curriculum as determinant of students’ learning outcomes at the junior secondary school one " (2015)
"Nigerian educators are concerned about the need to improve learners’ academic achievement in core subject areas (mathematics, English language, science, and social studies). Research, however, appears not to have focused on children who attended private primary schools in which other subjects are taught. This gap is what this study sought to examine by looking at how curriculum contents used by public and private primary schools affect learners’ performance. The study adopted the survey design. The population comprised of Nigerian children in junior secondary school 1 (JS1) who attended private primary school and those who did not. A total of 34 proprietors from 17 public and 17 private primary schools, and 680 students participated. These students were traced to their new schools. Five research instruments were used. Results revealed that private primary schools in Nigeria expose learners to extra subjects which are not recommended by the government. Significant differences exist in scores of learners exposed to extra subjects: mathematics exposed (x̅=75.3154, SD=12.98728) and not exposed (x̅=46.1100, SD=18.1); English language (x̅=74.11, SD=14.57) and not exposed (x̅ =53.15, SD=18.56); integrated science exposed (x̅=59.97, SD=15.1) and not exposed (x̅=44.51, SD=171); and social studies exposed (x̅=64.35, S.D=14.45) and not exposed (x̅=56.53, SD=18.03). The implications of these findings to educational practice in Nigeria were discussed. "